The Reicher-Wheeler paradigm in word recognition research: a cautionary note on its actual contributions and published misconceptions - Jordan, Timothy R.; Akkaya, Aziz M.; Göçmüş, Fatma Zehra; Kalan, Aleynanur; Morgul, Ebru; Önalan, Kübra; Sheen, Mercedes Kier (Frontiers in Psychology, 2024)
The study of word recognition has been influenced greatly by findings obtained when visual stimuli are presented very briefly. Under these conditions, a great deal of evidence suggests that words are perceived better than nonwords, and even single letters, and it is generally accepted that these "word superiority effects" reflect the relative efficiency with which words are perceived. For more than 50 years, a key procedure for establishing these effects has been the Reicher-Wheeler Paradigm in which potentially confounding effects of non-perceptual guesswork are cleverly suppressed. More recently, however, the actual nature of the Reicher-Wheeler paradigm and its contribution to research have become misrepresented in a range of publications, and its use in experiments has been confused and conflated with other, less sophisticated procedures. In this article we describe the actual contributions made by the Reicher-Wheeler Paradigm to word recognition research and show examples of how these important contributions have been misunderstood and misconceived in experiments reported in the recent literature.